Proposta de um modelo multicritério de apoio à tomada de decisão para exclusão de itens de portfólio em empresas de Product-Service System (PSS) - Ruiz, Guilherme Pires (Universidade Federal de São Carlos, 2026)
Given the increasing adoption of Product-Service Systems (PSS) by companies traditionally oriented toward products and considering the growing complexity in portfolio management resulting from this transition, this dissertation addresses the problem of deciding on the exclusion of underperforming offerings in a Brazilian energy company. Although the literature provides well-established contributions on portfolio management and product deletion, a gap remains regarding structured decision-support models specifically aimed at the exclusion of PSS in real-world organizational contexts. In light of this gap, the objective of this study is to propose and evaluate an MCDM-based decision-support model for the exclusion of portfolio items in a real case. The research was structured in two stages. First, a Systematic Literature Review (SLR) was conducted to identify the evolution of the topic and the lack of specific applications focused on PSS. Complementarily, the Design Science Research (DSR) approach was adopted for the development and application of a decision artifact integrating the Best-Worst Method (BWM), for defining criteria weights, and fuzzy-TOPSIS, for evaluating and ranking alternatives under linguistic uncertainty. The results demonstrate that the proposed model enabled the structured integration of strategic, financial, and operational criteria, reduced divergences among decision-makers, and generated a transparent ranking to support the exclusion of low-performing PSS offerings.
Proposal of a multicriteria decision-making support model for portfolio item exclusion in Product-Service System (PSS) companies
Keywords: Product-Service System; MCDM; Portfólio; Product Deletion; BWM; fuzzy-TOPSIS; ENGENHARIAS::ENGENHARIA DE PRODUCAO::PESQUISA OPERACIONAL; 12. Consumo e Produção Responsáveis